BUSINESS PROCESS MANAGEMENT TOOLS IN LARGE-SCALE AGRICULTURAL ENTERPRISES - Varfaliuk В. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The article explores the unique aspects of business process management in large-scale agricultural enterprises. It focuses not only on producing large quantities of agricultural products, but also on addressing issues of product quality and ecological impact related to the use of chemicals in farming. The process approach to managing business processes in large-scale agricultural enterprises is explained, starting with identifying the processes and then using tools to manage them. Key processes that affect product quality and interact with other processes are identified, along with allocating resources, designating responsible individuals,and developing methods to measure effectiveness. The article also proposes a classification of business processes for achieving commercial or social results, and it characterizes business processes related to added value and location. Business processes are defined as the interactions between production personnel, management teams, various resources, systems, and technologies, each yielding specific results for the enterprise. The article emphasizes that changing or supplementing any business process in a large-scale agricultural enterprise requires managerial influence and the use of specific tools including analysis and planning, execution, control, and improvement. These tools enable enterprises to make informed decisions to increase competitiveness and efficiency, understand customer behavior and market trends, adapt to a changing environment, and stimulate development. Finally, the article examines the concept of interactive planning as a modern tool for business process management, creating favorable conditions for the best development scenario for large-scale agricultural enterprises.